Temperature Correction of Broadband Power Detectors Based on Low-Barrier Diodes - V. G. Nechaev; A. S. Zagorodny; A. I. Dobrikov (Известия высших учебных заведений России: Радиоэлектроника, 2018)
The article is devoted to investigation of microwave power converter temperature dependence caused by changes in the current-voltage characteristic of diodes. The analytical expressions are given for such diode parameters as junction resistance and diode saturation current that allow to estimate temperature influence on diode detector output voltage. This paper presents a comparison of two methods, i.e. correlation based on a terminological method that works in con-junction with an arithmetic-logical mechanism. The first method implies that the temperature stabilizes by use of identical pair of diodes one of which compensates for temperature-induced changes of the second diode junction resistance. The second method involves formation of correction factors that allow performing temperature correction of measurement results in a wide range of capacities. Based on the conducted temperature tests of microwave power meters with the use of a temperature sensor in the microwave unit, the thermal correction algorithm was implemented. It allows to reduce the changes in the readings from ±15 to ±1.5%. Data from the results of experimental studies that can be used in measuring microwave equipment of various types. The results of experimental studies of detectors based on low-barrier diodes ZB-28 with a boundary speed exceeding 100 GHz and a tangential sensitivity of 1 nW are presented.